POLYMERIZATION OF AGAR JELLY ICE CUBE HYDROGEL FROM GRACILARIA SP. SEAWEED EXTRACT THROUGH PHYSICAL GELATION AS AN ALTERNATIVE FOOD COOLING MEDIA - Puspasari, Febriyati; Mustafa, Mustafa; Al Athaya, Muhammad Zada (Jurnal Chemurgy, 2026)
The suboptimal utilization of seaweed has the potential to cause environmental impacts and low added value for coastal communities, while the food industry still relies on conventional cooling media that are less sustainable. One alternative environmentally friendly material is agar from the seaweed Gracilaria sp. which is able to form a stable gel at room temperature. This study aims to determine the optimum conditions for the polimerization of the hydrogel "Jelly Ice Cube" based on Gracilaria sp. agar extract to obtain the best mechanical properties as an alternative cooling medium. The research method begins with the preparation of raw materials using 5% NaOH alkali treatment, followed by agar extraction at various temperatures (60, 70, 80, 90, and 100°C) with extraction times of 30 and 60 minutes. Hydrogel polimerization was carried out at room temperature with varying agar concentrations (2, 4, 6, 8, and 10%). Hydrogel characterization includes tensile strength and swelling ratio testing. The results showed that the combination of an extraction temperature of 90°C, a time of 60 minutes, and a concentration of 6% agar produced a hydrogel with the highest tensile strength of 90.23 kPa and a swelling ratio of 913.59%. Meanwhile, the highest swelling ratio of 1062.87% was obtained at an extraction temperature of 100°C, a time of 60 minutes, and a concentration of 2% agar, but with lower mechanical characteristics.